Voices from the Void: An Exploration of the Youthful Psyche in Arun Joshi’s Fiction - Md, Irshad (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
Arun Joshi, one of the most outstanding figures of Indian novelists in English, very brilliantly highlights the burning problems of the younger generation. The catch 22 situations of the modern youths are represented by the protagonists of Arun Joshi. The complexities of life have been explored very vividly by him. Obviously, his novels are an attempt to understand the world better. His novels delve into existentialism along with the ethical choices a man has to make. The element of utter chaos and discontentment among the modern youth has been pin -pointed.